Michel Foucault's Genealogical Analysis in Lajnah Bahtsul Masail Lirboyo's National Text Discourse in 1980 - Nailal Muna; Irgi Ahmad Vahrezi; Dwita Nurulita (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2024)
This research is within the large frame of the fiqh of nationality and examines Pancasila and Islamic values. This research examines the national fiqh text of Lajnah Bahtsul Masail (LBM) of Lirboyo Islamic Boarding School, Kediri, East Java, published in 1980. LBM of Lirboyo Islamic Boarding School is an academic tradition of the boarding school that produces problematic laws in society. LBM of Lirboyo Islamic Boarding School produces religious decisions that integrate Pancasila and spiritual values. This research is a Library research method with primary data from the LBM textbook published in 1980. The data analysis method uses Michel Foucault's genealogy of power theory. This research aims to discover the symbiosis of knowledge and power present during the emergence of the Lajnah Bahtsul Masail (LBM) national fiqh text. The conclusion of the research shows that the results of LBM were born from the micro genealogy in the form of the tradition of Islamic boarding schools and the fame of Islamic boarding schools, and macro genealogy in the form of political situations and national issues when the text was born.